Liposarcoma excision and removal with right total nephrectomy in a large retroperitoneal perinephric liposarcoma involving the right kidney: A case report - Bashir Lone, Showkat; Fatimah, Mehjabeen (Indian Journal of Case Reports, 2024)
An uncommon tumor, retroperitoneal liposarcoma (LPS) occurs in 2.5 out of every million people. Due to the lack of distinct clinical manifestations, early diagnosis is challenging. LPS is a mesenchymal tumor that is malignant and mostly develops into adipose tissue and is a common soft tissue tumor that affects people in their middle years. The thigh, gluteal region, retroperitoneum, leg, and shoulder area are among the areas that are frequently affected. Here, we report the case of a 72-year-old female who had a history of abdominal distension from the past 6 months, occasional retention of urine from the past 3–4 months, and constipation on and off from the past 1 year. The patient was evaluated and diagnosed with a case of right retroperitoneal LPS and treated by surgical resection. To sum up, retroperitoneal LPS is an uncommon condition involving other organs, though occasionally combined resection of other organs is also required.